Learning from experience - Schank, John F. (John Frederic), 1946-; Ip, Cesse; LaCroix, F. W.; Murphy, Robert E.; Arena, Mark V.; Kamarck, Kristy N.; Lee, Gordon T., 1953- (Rand Corporation monograph series., 2011)
Large, complex submarine design and construction programs demand personnel with unique skills and capabilities supplemented with practical experiences in their areas of expertise. Recognizing the importance of past experiences for successful program management, the U.S. Navy asked the RAND Corporation to develop a set of lessons learned from previous submarine programs that could help inform future program managers. This volume presents lessons from three submarine programs. The RAND team looked at how the programs were managed, the issues that affected management decisions, and the outcomes of those decisions. All three submarine programs had tenuous beginnings. Each experienced cost overruns and schedule delays in the construction of its first-of-class submarine. The Ohio and Virginia programs made corrections, and both are viewed as generally successful. Seawolf, probably due to the changing threat and budgetary environment, was terminated before changes could be made to correct early missteps. An overarching lesson from the three programs is the importance of program stability. Stability applies in many areas--funding consistency, a long-term build strategy, fixed operational requirements, program management, and an integrated partnership between the Navy and the shipbuilders.